Enhancing Childbirth Preparedness: The Effects of Prenatal Yoga on Physical nnd Mental Readiness - Santoso, Ferry; Hidayanti, Maria Ulfa Nur; Damanik, Brema JK; Novitasari, Prima; Karolina, Maria Estela (Jurnal Kesmas Jambi, 2025)
Childbirth requires both physical and mental readiness, yet many women face it with anxiety and insufficient preparation. Prenatal Yoga is increasingly recognized as a holistic intervention that integrates physical, psychological, and emotional preparation. This study aimed to examine the effect of Prenatal Yoga on the physical and mental readiness of pregnant women in facing childbirth. A cross-sectional quantitative study was conducted in May 2025 involving 54 pregnant women in Blora Regency. Data were collected using structured questionnaires to assess physical readiness (body flexibility and discomfort) and mental readiness (anxiety and relaxation) through the Hamilton Anxiety Rating Scale (HARS). The association between Prenatal Yoga and readiness was analyzed using Chi-Square and Fisher’s Exact tests. The study found no significant association between socio-demographic factors or yoga practice and physical readiness. In contrast, mental readiness was significantly associated with place of residence (p = 0.006), maternal education (p = 0.025), and participation in prenatal yoga (p = 0.000). Prenatal Yoga emerged as the strongest predictor of mental readiness for childbirth, highlighting its potential as a safe, accessible, and effective strategy to reduce anxiety, enhance self-efficacy, and improve emotional resilience. Promoting Prenatal Yoga within maternal health programs may empower women to face childbirth with greater confidence and mental preparedness.